PERBANDINGAN HAK PENGUASAAN ATAS TANAH ANTARA NEGARA INDONESIA DENGAN NEGARA KEPULAUAN SOLOMON - Dhea Nadhifa Vrily Pontoh; Dinda Keumala (Reformasi Hukum Trisakti, 2021)
Comparative Law is the confrontation of comparable elements of two legal systems to find their differences and similarities. Land tenure rights in Indonesia and Solomon Islands. The formulation of the problem is; what are the similarities and differences between the Land Tenure Rights between the State of Indonesia and the Solomon Islands? and what are the factors causing differences in Land Tenure Rights between the State of Indonesia and the Solomon Islands? The method of legal research is normative and is descriptive-comparitive, secondary data which is analyzed qualitatively, and the conclusion is drawn using the deductive method. The results of this research, discussion and conclusion are, there are similarities in Indonesia and the Solomon Islands regarding land tenure rights, namely the meaning of land tenure rights, the existence of customary land tenure rights, individual rights to land in the form of property rights & perpetual estate, and arrangements for the subject of land rights holders. In addition to similarities, differences arise in the form of regulation of land tenure rights, the use of hierarchy in land tenure rights, systematics in land tenure rights in the form of state control rights with public (crown) land.